Minimization of real power loss by enhanced teaching learning based optimization algorithm - Lenin, K. (Institute of Advanced Engineering and Science, 2020)
This paper presents an Enhanced Teaching-Learning-Based Optimization (ETLBO) algorithm for solving reactive power flow problem. Teaching-learning process is an iterative process where in the continuous interaction takes place for the transfer of knowledge. Movements of trial solutions will investigate the internally final stages. Up gradation of the algorithm has been done through by adding weight in the learner values. Projected ETLBO algorithm has been tested in standard IEEE 57,118 bus systems and power loss has been reduced efficiently.